Production and characterization of lightweight aggregates from municipal solid waste incineration fly-ash through single- and double-step pelletization process. (10th January 2023) - Ferraro, Alberto; Ducman, Vilma; Colangelo, Francesco; Korat, Lidija; Spasiano, Danilo; Farina, Ilenia
Abstract: The performance of a cold-bonding pelletization process was investigated for lightweight aggregates (LWAs) production from municipal solid waste incineration (MSWI) fly-ash (FA), by including multiple waste materials in the aggregate mixture. Before pelletization, FA was pre-treated by washing with water, which led to a reduction of chloride (66.79%) and sulphate (25.30%) content. This was further confirmed by XRF and XRD analyses, which showed a reduction of chloride elements and the content of chlorine crystalline phases. The pelletization process was carried out using both single- and double-step methods. For single-step pelletization, all the mixtures contained 80% FA, combined with various compositions of cement (5, 10, and 15%) and granulated blast furnace slag (GBFS) (5, 10, and 15%). For the double-step pelletization 30% of cement and 70% of marble sludge (MS) were added to each of the previous mixtures. The apparent density of all the aggregates varied between 1.60 and 1.87 g cm −3, suggesting their suitability to be classified as LWAs. Aggregates produced from double-step pelletization showed improved characteristics, with water absorption capacity and open porosity generally lower compared to the corresponding aggregates from the single-step pelletization. The best values of compressive (crushing) strength (almost 11 MPa) were observed for double-step pelletization aggregates with initial cement: GBFS mixture of 15%:5%. Results from leaching tests showed an overall significant release of chloride and sulphate. Nevertheless, leaching from double-step pelletization aggregates was reduced by 1.73-4.02 times for chloride and 1.58-5.67 times for sulphate, further suggesting that better performances are achievable through the addition of an aggregate second layer. Graphical abstract: Image 1 Highlights: Cold-bonding granulation was performed for aggregates production from MSWI fly-ash. Water washing was investigated as fly-ash pre-treatment for soluble salts removal. Multiple wastes were involved in the aggregate mixtures for higher waste reuse rate. Double-layer aggregates were produced through a double-step pelletization technique. Enhanced mechanical/structural properties were observed for double-layer aggregates.